Modulation of Molybdenum oxidation state via Catalytic-oxidation - Lee, Kangchun; Sun, Seho; Ko, Hyunseok; Beom Cho, Sung; Lee, Ganggyu; Lee, Dongsoo; Song, Taeseup; Paik, Ungyu (Applied Surface Science, 2023)
Molybdenum (Mo) is a promising metal contact material to replace tungsten due to its low electrical resistivity in sub-3 nm next-generation semiconductor processes. However, the high dissolution rate of Mo during the chemical mechanical planarization (CMP) process limits its practical introduction because it deteriorates surface flatness and consequently causes decisive device failure. Herein, we report a strategy to suppress Mo dissolution by manipulating the oxidation state of Mo film via catalytic-oxidation reaction. Adoption of Fe catalyst under the trace amounts of H2O2 enables the formation of insoluble MoO2 and Mo2O5 phases while minimizing the generation of the soluble MoO3 phase. The dissolution behaviors of Mo at various oxidation states were investigated according to both oxidizer and catalyst concentrations during the CMP process. To identify the detailed dissolution phenomena of Mo, the Gibbs free energies and dissolution kinetics in different Mo oxide phases were validated using density functional theory (DFT) calculation. We successfully confirmed that catalytic-oxidation using Fe ions achieved an enhanced removal rate from 780 to 1500 Å/min, even though the dissolution rate was minimized from 636 to 57 Å/min compared to a single oxidation reaction. We believe that our results, supported by theoretical considerations and experimental results, can elucidate Mo oxidation and dissolution phenomena for application to the advanced semiconductor manufacturing processes.
Keywords: Chemical-mechanical planarization; Chemical-mechanical planarization process; Contact material; Dissolution kinetics; High dissolution rate; Metal contacts; Middle-of-line; Oxidation reactions; Oxidation state; Semiconductor process; Catalytic-oxidation; Chemical mechanical planarization; Dissolution kinetics; Middle-of-line (MOL); Molybdenum; Oxidation state